Konsultasi Publik dalam Penyusunan KLHS RPJPD Aceh Jaya 2025–2045: Kajian Partisipatif - Lestari, Rachmatika; Yana, Rahmah Husna (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2025)
The preparation of the Strategic Environmental Assessment (SEA) in the Regional Long-Term Development Plan (RPJPD) is a crucial step to ensure that environmental aspects are integrated into all stages of development planning. This study aims to examine the public consultation process in the preparation of the SEA for the Aceh Jaya RPJPD 2025–2045, as an application of a participatory approach oriented toward sustainability and social justice. The research uses a qualitative approach through participatory observation, in-depth interviews, and documentation of public consultation activities involving stakeholders from government, academia, civil society, traditional leaders, and local youth. The findings show that public consultation enhances transparency in planning processes, increases inclusivity in decision-making, and fosters a sense of ownership among the community regarding the region’s development direction. However, challenges remain in optimizing meaningful participation, such as limited participant capacity and time constraints for discussion. This study emphasizes the importance of strengthening local capacity, adaptive facilitation, and developing feedback mechanisms as integral components of the SEA process. Furthermore, the study reflects the role of higher education institutions in accompanying transformative development processes through science-based community service. Thus, public consultation is not merely a legal-formal procedure but a strategy for community empowerment toward sustainable and participatory development.